Studying inclusive innovation with the right data: An empirical illustration from Ethiopia - Alemu, Solomon; Kosmowski, Frederic; Stevenson, James R.; Mallia, Paola; Taye, Lemi; Macours, Karen (Elsevier, 2024)
CONTEXT Agricultural innovations are inclusive when they are used by any member of society who wants to use them. Conversely, agricultural innovations that can only be used by a specific privileged group within society can be characterized as “exclusive”.